2005
DOI: 10.1002/erv.651
|View full text |Cite
|
Sign up to set email alerts
|

Adults with chronic eating disorders. Two-year follow-up after inpatient treatment

Abstract: Objective: The aims of this prospective study were (1) to report on the 2-year outcome of chronically ill adult eating disorder patients, (2) to investigate whether a specialized inpatient treatment might influence the course of the illness, and (3) to search for prognostic factors. Method: Seventy-two patients were treated in a 4-5-month specialized group treatment programme for chronically ill adults with eating disorders. Sixty-five (90%) with mean age of 30 years were available for the follow-up assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
(42 reference statements)
3
11
0
Order By: Relevance
“…Various predictors of poor outcome in BED have included higher palliative reacting to problems (using distraction or self-comforting behaviors), 14 more interpersonal problems, 15 sexual abuse history, 18 and psychiatric comorbidity. 18 In studies of other EDNOS or in samples with mixed diagnoses, low BMI and AN diagnosis have emerged as poor prognostic indicators, 1,22 supporting previous findings that AN is associated with a more chronic course compared to other eating disorders. 30 An additional poor prognostic indicator identified for EDNOS was absence of close friends.…”
Section: Prognostic Factorsmentioning
confidence: 73%
See 1 more Smart Citation
“…Various predictors of poor outcome in BED have included higher palliative reacting to problems (using distraction or self-comforting behaviors), 14 more interpersonal problems, 15 sexual abuse history, 18 and psychiatric comorbidity. 18 In studies of other EDNOS or in samples with mixed diagnoses, low BMI and AN diagnosis have emerged as poor prognostic indicators, 1,22 supporting previous findings that AN is associated with a more chronic course compared to other eating disorders. 30 An additional poor prognostic indicator identified for EDNOS was absence of close friends.…”
Section: Prognostic Factorsmentioning
confidence: 73%
“…Overall, results from these studies are consistent with those reported earlier. Among individuals who predominantly have full-threshold AN or BN at intake, a considerable proportion migrate to a diagnosis of EDNOS at follow-up, 22,23 and rates of remission appear to increase with duration of follow-up. 23 However, at 10-year followup, 26 a considerable minority of individuals continue to report a diagnosable eating disorder suggesting a chronic course for eating disorders in a third of individuals ascertained through inpatient settings.…”
Section: Heterogeneous Samplesmentioning
confidence: 90%
“…We reported that in a sample of 62 patients with chronic EDs, 86% still had an ED or a subthreshold ED at 2-year follow-up although 71% had improved (Rø, Martinsen, Hoffart, Sexton, & Rosenvinge, 2004). In the current study, we expanded the series and studied the course of PDs and 57 of the sample of 74 patients had one or more comorbid PDs at admission.…”
Section: Discussionmentioning
confidence: 91%
“…In a previous paper (Rø, Martinsen, Hoffart, Sexton, & Rosenvinge, 2004), we reported the course of ED symptoms at 2-year follow-up after inpatient treatment of 65 patients with chronic EDs. At the 2-year follow-up, 71% of the patients were improved, including 14% who were recovered.…”
Section: Introductionmentioning
confidence: 98%
“…Both the American Psychiatric Association (APA) guidelines [1], and the National Institute for Health and Care Excellence (NICE) guidelines [2], recommend inpatient treatment as one treatment option in cases of severe illness (psychological and medical symptoms), enduring illness, and unsuccessful outcome of treatment. Symptom improvement during inpatient treatment of adult patients with an ED enrolled in different treatment programs has been reported [3][4][5][6][7][8][9][10][11], and findings showed that improvement was mainly sustained at follow-up [3,6,[8][9][10][11]. However, outcome after inpatient treatment is reported as poor [12].…”
Section: Introductionmentioning
confidence: 99%